Pengaruh Leverage, Likuiditas, Profitabilitas, Umur Perusahaan dan Ukuran Perusahaan Terhadap Kualitas Laporan Keuangan (Study Empiris pada Perusahaan Manufaktur Sektor Makanan & Minuman Yang Terdaftar di Bursa Efek Indonesia Periode 2018 – 2021) - Vegi Caisar Pratama; Rina Asmeri; Andre Bustari (Ekasakti Pareso Jurnal Akuntansi, 2024)
This study aims to examine the effect of Leverage, Liquidity, Profitability, Company Size and Company Age on the Quality of Financial Statements in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2021 period. The population of this study consisted of 32 manufacturing companies listed on the Stock Exchange and the sampling method was carried out by purposive sampling. With this method, a sample of 15 companies was obtained with an observation period of 4 years (2018-2021) so that the number of observations was 60. The annual report data is accessed through the Indonesia Stock Exchange website (www.idx.co.id).Variable Quality of Financial Statements is measured by the Multiple Linear Regression Formula measured by the total Variable x, Variable x Leverage is measured by DAR = Total Debt: Total Assets, Liquidity is measured using the formula Current Ratio = Current Assets: Current Liabilities, Profitability is measured using the formula ROA = Net income after tax: Total assets, company size is measured using the formula Company Size = Ln Total assets, company age is measured using the formula Company age = Research year. The data used in this research is quantitative data. The data collection technique used in this research is the proportional sampling method. The data analysis technique used multiple linear regression analysis.The results showed that: 1) Leverage had a partial effect on the quality of financial statements, 2) Liquidity had a partial effect on the quality of financial statements, 3) Profitability had a partial effect on the quality of financial statements, 4) Company size had a partial effect on the quality of financial statements, 5) Age The company partially influences the quality of financial statements, and Leverage, Liquidity, Profitability, Company size and company age Simultaneously influence the quality of financial statements